Study on the chain-type failure mechanism of large-scale ancient landslides - Li, Zixuan; Dai, Zhenwei; Cheng, Shi; Yang, Zhe; Zhang, Anle; Xiong, Qihui (Frontiers in Earth Science, 2024)
Large-scale ancient landslides are widely distributed in Southwest China, yet their reactivation mechanisms remain complex and poorly understood. On 25 July 2020, one such landslide in Liujing Village, Wulong District, Chongqing, China, experienced reactivation. This event exhibited variable movement characteristics across different areas and times, ultimately manifesting as a chain-type failure. Combining field investigations and drilling works, this study describes the fundamental characteristics of the Zhongbao landslide and the variation rules of the seepage field and the stability by numerical simulations. The failure mechanism is preliminarily revealed, and the failure influencing factors are discussed. The results show that, the landslide’s progression was influenced by the stratigraphic lithology and the morphology of the sliding surface, resulting in two distinct turns during its movement. By analyzing the landslide’s spatial morphology, direction of sliding, material composition, extent of the accumulation area, and dynamic behavior, we have categorized the Zhongbao landslide into five principal zones. The failure process can be segmented into four stages: initiation, shear-out, acceleration, and accumulation blockage. Heavy rainfall served as the primary trigger for the landslide, while the microtopography of the sliding surface significantly influenced the failure dynamics. The insights gained from this study offer valuable guidance for understanding the reactivation mechanisms of similar chained ancient landslides in the geologically analogous regions of Southwest China.